2021
DOI: 10.1108/jpbm-01-2020-2731
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumers’ attitude formation toward their own brands when in crisis: cross-national comparisons between USA and China

Abstract: Purpose This study aims to examine how culture influences consumer attitudes toward the brands of products they own during a product-harm crisis. To this end, average consumers from two countries - the USA, representing a highly individualistic society and China, a less individualistic (i.e. collectivist) society – are compared. Design/methodology/approach The study conducts an invariance test of the measurement model for a more rigorous comparison of the two countries. Structural equation modeling is perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 110 publications
1
11
0
Order By: Relevance
“…In contrast, a values crisis refers to a brand’s involvement in environmental, social or ethical issues that challenge its ability to deliver symbolic benefits. Given the rise of unpredictable and multifaceted issues in the global marketplace, effective brand crisis management has become increasingly critical (Kim and Yim, 2022; Pearson and Mitroff, 2019). Despite the frequency of such brand crises and their potentially catastrophic consequences, research in this area remains relatively fragmented (Baghi and Gabrielli, 2019; Gkouna et al , 2022; Kuipers and Wolbers, 2021; Pyke et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a values crisis refers to a brand’s involvement in environmental, social or ethical issues that challenge its ability to deliver symbolic benefits. Given the rise of unpredictable and multifaceted issues in the global marketplace, effective brand crisis management has become increasingly critical (Kim and Yim, 2022; Pearson and Mitroff, 2019). Despite the frequency of such brand crises and their potentially catastrophic consequences, research in this area remains relatively fragmented (Baghi and Gabrielli, 2019; Gkouna et al , 2022; Kuipers and Wolbers, 2021; Pyke et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To sum up, even though culture is known to shape a person’s values, utility importance and preferences (De Mooij, 2019; Kim and Yim, 2021), we revealed that in the brand selection context, which is more cognitively demanding than single choice evaluation, the internal process of brand choice seems to be similar across cultures.…”
Section: Introductionmentioning
confidence: 67%
“…The literature on consumer behavior has long documented cultural differences in perceptions, attitudes and purchasing decisions (De Mooij, 2019; Kim and Yim, 2021 Oh et al .,2020; Swoboda and Sinning, 2020).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Second, enterprises can lose consumers because of low perceived value and the loss of reputation brought about by product-harm crises (Kim and Yim, 2021; Zhang and Zhou, 2020). Approaches for managing such crises have been suggested, such as: resolute denial, forcible recalls or active recalls (Siomkos and Kurzbard, 1994; Lee, 2020; Yuan et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, consumers try to determine why the product has failed and the reason they infer affects their attitudes and behavior toward the brand. When the crisis is determined to be intentional, consumers are more willing to complain and their evaluation of the brand deteriorates (Kim and Yim, 2021; Moisio et al , 2021), whereas when the crisis is deemed to be accidental, consumers are more inclined to be forgiving (Puzakova et al , 2013; Srinivasan and Sarial-Abi, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%